2020
DOI: 10.1055/s-0040-1705263
|View full text |Cite
|
Sign up to set email alerts
|

Image Guided Percutaneous Cholecystostomy–A Single Center Experience

Abstract: Purpose To assess the technical feasibility of percutaneous cholecystostomy (PCC) for acute cholecystitis and formulate an algorithm for PCC. Materials and methods This is a retrospective study of 35 patients (28 male and 7 female; mean age 60 years) who underwent image-guided PCC from 2008 to 2018 at a tertiary care hospital in South India. Descriptive summary statistics and frequencies were used to assess the technical success and complications. Results The patients (35/35) presented with fever, abdominal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…64 The authors concluded that PC assists in resolution of sepsis and prepares patient for early cholecystectomy. Similar results were found by another study by Narayanan et al 65 In a randomized controlled trial (RCT) by Hatzidakis et al, in 2002, the authors found that, in high-risk patients, PC was not better than conservative management in terms of clinical improvement and 30-day mortality. 66 However, they suggested to perform PC in patients who fail to respond to conservative treatment within 3 days.…”
Section: Methodssupporting
confidence: 82%
“…64 The authors concluded that PC assists in resolution of sepsis and prepares patient for early cholecystectomy. Similar results were found by another study by Narayanan et al 65 In a randomized controlled trial (RCT) by Hatzidakis et al, in 2002, the authors found that, in high-risk patients, PC was not better than conservative management in terms of clinical improvement and 30-day mortality. 66 However, they suggested to perform PC in patients who fail to respond to conservative treatment within 3 days.…”
Section: Methodssupporting
confidence: 82%